Bilayered Muco-Adhesive Delivery System For Extended Release Of Bisphosphonates - D.J.MUKHERJEE; S.BHARATH; V. MADHAVAN (International Journal of Pharma and Bio Sciences, 2012)
Bisphosphonates are used against osteoporosis and Paget’s disease. Despite their benefits; bisphosphonates suffers from poor oral bioavailability (1-2%). Bilayered multipolymeric films comprising of risedronate sodium with chitosan (85% deacetylated) and hydroxypropylmehtyl cellulose (HPMC 4KM) interpolymer complex of different ratios were prepared by solvent casting method. An impermeable backing membrane of ethyl cellulose was incorporated in to the films. The films were studied for swelling degree, moisture uptake, viscosity, folding endurance, water vapor transmission rate and mucoadhesive time. The prepared films demonstrated uniform and reproducible drug content (99.67±0.023-100.31±0.056%), thickness (0.286±0.032-0.443±0.051mm), mucoadhesivity (7.91±0.295-11.806±0.379 g) and sustained drug release profile up to 8 hours. The delayed release of the drug is probably as a result of combined effect of ethyl cellulose hydrophobicity, gel-forming property of HPMC and interpolymer complexation of chitosan and HPMC 4KM. The study confirms the potential of bilayered, interpolymer complex films as a promising candidate for buccal delivery of bisphosphonates.